2014
DOI: 10.1175/mwr-d-14-00076.1
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Lightning Data Using a Nudging Method Involving Low-Level Warming

Abstract: This study presents a new method for assimilating lightning data into numerical models that is suitable at convection-permitting scales. The authors utilized data from the Earth Networks Total Lightning Network at 9-km grid spacing to mimic the resolution of the Geostationary Lightning Mapper (GLM) that will be on the Geostationary Operational Environmental Satellite-R (GOES-R). The assimilation procedure utilizes the numerical Weather Research and Forecasting (WRF) Model. The method (denoted MU) warms the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 91 publications
(90 reference statements)
0
26
0
Order By: Relevance
“…The slightly higher bias in NoSuppress compared to CTRL results from forcing deep convection in lightning grid cells without suppressing incorrectly placed convection, leading to excess rainfall. Similar increased biases have been seen in convective-permitting WRF simulations that used lightning assimilation without suppression [e.g., Fierro et al ., 2012 ; Fierro et al ., 2015 ; Marchand and Fuelberg , 2015 ]; however, suppression techniques become more complicated when convection is explicitly resolved.…”
Section: Results For Warm-season Cases: July 2012 and July 2013mentioning
confidence: 99%
“…The slightly higher bias in NoSuppress compared to CTRL results from forcing deep convection in lightning grid cells without suppressing incorrectly placed convection, leading to excess rainfall. Similar increased biases have been seen in convective-permitting WRF simulations that used lightning assimilation without suppression [e.g., Fierro et al ., 2012 ; Fierro et al ., 2015 ; Marchand and Fuelberg , 2015 ]; however, suppression techniques become more complicated when convection is explicitly resolved.…”
Section: Results For Warm-season Cases: July 2012 and July 2013mentioning
confidence: 99%
“…In the Fierro et al studies the Q v increase was confined at midlevels within the graupel‐rich, mixed phase region between 253 K and 273 K. In this study, however, Q v was increased over a slightly deeper layer rooted at lower levels, namely, between 285 K and 261 K. These isotherms correspond, respectively, to the lifted condensation level and the level of maximum vertical velocity. This change was motivated by the findings of Marchand and Fuelberg [] and Fierro et al [], which suggest that increasing Q v in the lower troposphere (below 700 hPa) instead of the mixed‐phase region allows convection to become more quickly rooted in the PBL and, in turn, better represents weakly forced moist convection. The value of C is based on the gridded number of flashes.…”
Section: Model Setupmentioning
confidence: 99%
“…The first studies, which investigated means to assimilate total lightning data at convection‐allowing and convection‐resolving scales, were reported by Fierro and Reisner () and Fierro et al (, 2014), wherein incremental increases in water vapor mass were applied in the mixed‐phase region to locally enhance thermal buoyancy, which, ultimately, promoted the development of updrafts at observed lightning locations. Marchand and Fuelberg () used a temperature nudging method to warm the boundary layer to hasten the development of convection where lightning flashes are observed. Qie et al () employed the nudging function of Fierro et al () to adjust ice‐phase hydrometeor mass where lightning was observed.…”
Section: Introductionmentioning
confidence: 99%